Arbitration and human rights: synergy or parallel (2016)
The crux of this paper ¡s to examine arbitraron agreement from the perspective of the question of whether or not it is not a violation of human rights of access to court. To tackle this vexed question, the paper first considers the legal framevvork for arbitration agreement from the viewpoint of waiver of the right to State administered justice. The paper analyses the relationship between human rights and arbitration proceedings with a view to determine whether arbitration agreement is not an encroachment on human rights? Corning down to Africa, this paper examines whether or not arbitration is antithetical to the human rights provisions ¡n the various African constitutions on access to courts, fair and public hearing of disputes and public delivery of judgment. The paper argües that arbitration does not breach these rights and that recourse to arbitration is a waiver of the parties' rights of access to court. The paper concludes that arbitral tribunals do not fall into category of courts and tribunals vvhich African legal system requires to hold public hearing and public delivery of judgments or findings. The paper therefore takes position that arbitration and human rights are different means to the same end.